Pengaruh Kesadaran Literasi Pada Praktek Keberagamaan: Studi Gerakan Literasi dan Al-Qur’an pada Perempuan - Budi Utomo (Ad-DA'WAH, 2022)
The variety of teaching methods for recognizing the letters of the Qur'an in Indonesia is a development of the parent method, namely Baghdadiy. Generally, the development of this method offers a practical way of teaching and short learning duration. Unfortunately, this results in the loss of the letter recognition process perfectly, because the letters have certain detailed characters, so that students feel they have completely mastered how to read the Qur'an. Another problem is that textbooks of teaching materials that are applied can sometimes be used without having to go through the development agency, so that teachers do not carry out the learning process according to the official procedures of the method development institution. This development is still focused on how to read, not on the ability to write, and enter the spirit of the Qur'an. As a textbook, the early generations of Baghdadiy contained a systematic learning method, requiring only a few touches and instructions for use. The additions needed are advanced competencies, namely writing and understanding.